Peran Penguasaan Teknologi, Kualitas Sumber Daya Manusia, dan Tingkat Upah Terhadap Permintaan Tenaga Kerja Di Pulau Jawa - Kurniawan, Heru (IAIN Syekh Nurjati Cirebon, 2024)
Uneven demand for labor in Java Island causes economic inequality. this study aims to determine how the influence of technological mastery, the quality of human resources, and the level of wages on labor demand on the island of Java. this study uses qualitative methods with panel data, through model selection followed by model feasibility tests and classical assumption tests. The result of this research is known that XI with Prob. 0.0321 <0.05, then X1 has a significant effect on Y, for X2 with a Prob value. 0.0000 less than 0.05, then X2 has a significant effect on Y, and X3 with a prob value. This study concludes that mastery of technology can increase the demand for labor but hurt the decline in the demand for ordinary labor. the quality of human resources has a positive effect on the demand for labor on the island of Java and the level of wages hurts the demand for labor, when wages rise, the demand for labor will decrease. To equalize the demand for labor in Java, the government must equalize the development of good public facilities, easy access, and superior training, so that entrepreneurs are interested in building new economic sectors in areas in Java. thus the demand for labour will occur evenly not only in big cities but also in other regions.